2014
DOI: 10.1007/s13311-014-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Type 2 Activation Induces Neuroprotection and Neurogenesis After Traumatic Brain Injury

Abstract: Angiotensin II receptor type 2 (AT 2 ) agonists have been shown to limit brain ischemic insult and to improve its outcome. The activation of AT 2 was also linked to induced neuronal proliferation and differentiation in vitro. In this study, we examined the therapeutic potential of AT 2 activation following traumatic brain injury (TBI) in mice, a brain pathology that displays ischemia-like secondary damages. The AT 2 agonist CGP42112A was continuously infused immediately after closed head injury (CHI) for 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 85 publications
1
32
0
Order By: Relevance
“…The results implied that a potential association might exist between S1PR1 activation and MEK/Erk cascade phosphorylation in hippocampal neurogenesis after TBI. In addition to our findings, other studies have shown that the upregulated expression of pErk at 8 hours, 1 day, and even 14 days after CNS injury also played a positive role in hippocampal neurogenesis [31, 32, 37]. Accordingly, these evidences collectively provided an insight into the regulatory role of MEK/Erk signaling in neurogenesis after TBI.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results implied that a potential association might exist between S1PR1 activation and MEK/Erk cascade phosphorylation in hippocampal neurogenesis after TBI. In addition to our findings, other studies have shown that the upregulated expression of pErk at 8 hours, 1 day, and even 14 days after CNS injury also played a positive role in hippocampal neurogenesis [31, 32, 37]. Accordingly, these evidences collectively provided an insight into the regulatory role of MEK/Erk signaling in neurogenesis after TBI.…”
Section: Discussionsupporting
confidence: 84%
“…In several previous studies, it was well acknowledged that MEK/Erk cascade was critical for the activation of transcription factors and genes to regulate NSCs proliferation and differentiation, as well as the maturation of NSCs-derived neuronal cells [18, 31, 32]. Recently, growing researches have demonstrated an involvement of MEK/Erk cascade in neurogenesis induced by diverse growth factors, such as neurotrophin-3 and vascular endothelial growth factor (VEGF) [3335].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, post-TBI hypothermia treatment increases survival of newly generated neurons (Bregy et al, 2012). Intraventricular infusion of angiotensin receptor type 2 agonist (CGP42112A) for 3 days following a closed head injury induces cell proliferation in both the SVZ and DG, and increases the total number of new neurons in a dose-dependent manner (Umschweif et al, 2014). Post-TBI treatment with the P7C3 class of aminopropyl carbazole agents (P7C3-A20) 30min post LFPI for 7 days increases cell proliferation and survival of newly generated neurons in the SGZ (Blaya et al, 2014).…”
Section: Enhancement Of Endogenous Neurogenesis As Potential Therapeumentioning
confidence: 99%
“…Activation of AT2 increases the expression levels of BDNF and its receptors in neurons (Namsolleck et al, 2013). Activating AT2 via pharmacological agent CGP42112A in a closed head injury model in mice via intraventricular infusion for 3 days immediately following injury shows a dose dependent improvement in functional recovery accompanied by enhanced cell proliferation and generation of new neurons in the DG (Umschweif et al, 2014a & 2014b). …”
Section: Existing Fda Approved Drugsmentioning
confidence: 99%